Measuring effectiveness and critical success factors for successful enterprise architecture management capabilities in South Africa. - Kingsley, Gregory Michael (My University, 2016)
Many organisations are currently pursuing the promised benefits of enterprise architecture management (EAM). In order to achieve this they have implemented EAM capabilities, however, many of these organisations do not know if these investments are actually providing any value for them and their shareholders. In addition, there is limited academic research into the topic of enterprise architecture as a whole and even less is available on critical success factors for effective enterprise architecture management. This study was conducted in an attempt to determine how organisations should measure the effectiveness or value of their EAM capabilities and to discover what the underlying critical success factors are in ensuring EAM effectiveness. A review of existing literature was conducted in order to establish a theory base which was then used when conducting a qualitative research exercise comprising of semi-structured one-on-one interviews with 17 EAM practitioners whom all have had experience with enterprise architecture. Various content analysis techniques were employed including concept coding and thematic abstraction. Ontological cognitive mapping was used to analyse the resulting concept maps of the critical success factors. The findings of the research are that organisations should measure the effectiveness of their EAM capabilities. The most relevant measures for EAM value are measures which reflect the overall organisation’s performance however the exact choice of measures is highly dependent on the context that the EAM capability operates in. Two predominant factors influence this context, maturity and scope. Additional measures are also provided including costs, agility, reliability and internal EAM capability measures. The critical success factors identified included: focusing EAM primarily on the business, soft skills, support generating outcomes, technical execution of the EAM capability, structure and accountability of EAM, governance, successful delivery of iii valuable change and trust. A key message of the critical success factors is the focus on business and business priorities.
MBA
Keywords: Management information systems. Business -- Data processing. Information technology -- Management.Organizational effectiveness -- South Africa.